Do young female dancers improve symptoms and return to dancing after periacetabular osteotomy for the treatment of symptomatic hip dysplasia? - Novais, Eduardo Nilo; Thanacharoenpanich, Songkiat; Şeker, Ali; Boyle, Matthew; Miller, Patricia E.; Bowen, Garrett; Millis, Michael B.; Kim, Young-Jo (Oxford University Press, 2018)
Although preservation of high activity level has been reported in active young patients after periacetabular osteotomy (PAO) for the treatment of symptomatic hip dysplasia, there is limited evidence whether a dancer may be able to resume dancing after PAO. We asked whether female dancers experience improvement in pain and sports-related activities and return to dance following PAO. Between 1997 and 2014 we performed a total of 44 PAOs in 33 female dancers with symptomatic hip dysplasia. The mean age was 20.3 years (SD 5.6 years) and the median follow-up was 2.7 years (IQR 1.7-5.9 years). The Hip Disability and Osteoarthritis Outcome Score (HOOS), the modified Harris hip score (MHHS) and hip motion were collected preoperatively and at most recent follow-up. Return to dance was recorded from self-reported questionnaires and medical record review. Female dancers reported an improvement in HOOS total scores of nearly 20 points (P = 0.007) and MHHS improved over 17 points (P = 0.01) from preoperative to most-recent follow-up. Out of the 30 patients for whom information about return to dance was available, 19 (63%; 95% CI = 43.9-79.5%) had returned to dance at an average of 8.8 months (+/- 3.6 months) after PAO. With the numbers available we did not identify any factors associated with returning to dance in this cohort. Improvement in hip pain, sports-related activities and hip function may be expected following PAO in young female dancers. Most female dancers can expect to return to dance during the first year after surgery.
WOS: 000449501200008
PubMed ID: 29876131
Keywords: Professional Ballet Dancers; Motion; Intermediate; Predictors; Joint